School Well-Being pada Mahasiswa dan Perspektif Keislaman - Alfikri, Muzaki; Hidayat, Bahril (Al-Hikmah: Jurnal Agama dan Ilmu Pengetahuan, 2025)
The activities that occur at school will have an impact or influence on the level of comfort and sense of security of students when at school. One of the places of educational institutions is campus. So that the campus becomes one of the places that students expect to be able to provide comfort and a sense of security when students are on campus, environmental comfort will be related to student health, both physically and mentally with a positive social environment. The purpose of this article is to describe the condition of school well-being at school or on campus based on psychological theory and Islamic perspectives. This article focuses on previous data collection so that it uses the Library Research method or library research method which is a method of collecting data through library data. In this case, educational media facilities must pay attention to the environment and facilities provided, school well-being has four aspects in it that can influence the achievement of school well-being, namely the aspects of having, loving, being and health. Several research results show that the aspect of having or the school environment greatly influences school well-being in students or students, but other aspects are also supporting aspects in school well-being. The perspective according to Islam has similarities with the aspect of having, namely creating a comfortable environment such as the facilities provided, easy-to-understand learning methods, so that what distinguishes the Islamic perspective from other perspectives is its source which comes from the Qur'an and hadith.